The 'bridge effect' by intermediate hosts may explain differential distributions of Echinococcus species. Issue 7 (July 2022) - Massolo, Alessandro; Simoncini, Andrea; Romig, Thomas
Abstract : Zoonotic cestodes of the genus Echinococcus show marked differences in their distribution patterns which have not been satisfactorily explained. Echinococcus multilocularis is limited to the Holarctic, whereas species in the Echinococcus granulosus sensu lato ( s.l. ) complex mostly have a worldwide distribution. We proposed and tested a 'bridge effect' hypothesis stating that the low virulence of species in the E. granulosus s.l. complex for their intermediate hosts and a longer lifespan of infected hosts explain the differential distributions, particularly in hot and dry regions. This does not exclude the contribution of other factors such as human-mediated dispersal and intermediate host distribution. In the light of globalization and climate change, understanding what drives the distribution of zoonotic parasites is critical for preventing outbreaks of disease caused by these pathogens. Highlights: Understanding the drivers of differential distributions in zoonotic parasites is essential to prevent pathogen outbreaks under global change. Species in the Echinococcus granulosus sensu lato ( s.l. ) complex are mostly cosmopolitan, occurring in a wide range of conditions, whereas Echinococcus multilocularis is limited to the Holarctic. We developed the 'bridge effect' hypothesis, according to which the lower pathogenicity of E. granulosus s.l. species for intermediate hosts with a longer lifespan determines the observed distributional differences. A critical review of the literature provided support for the 'bridge effect' hypothesis and suggested a concurrent role of human-aided dispersal and intermediate host distribution.